A Quantitative Measurement Model for Persuasive Technologies Using Storytelling via a Virtual Narrator. Issue 17 (20th October 2020) - Faddoul, Guillaume; Chatterjee, Samir
ABSTRACT: The study of persuasive techniques associated with technology is an important part of behavioral change research in information systems. Applied in areas such as education and healthcare, persuasive messages usually contain guidelines the users must follow in order to reach the targeted new behavior. We are studying the use of storytelling and virtual reality as persuasive methods. Those two techniques appear in several studies, together or separately. We base our study on an analysis of the current literature and a two steps survey combining 528 participants with valid responses. A factor analysis allowed us to develop a model measuring the persuasive effectiveness of storytelling via virtual narrator. This model is based on 31 items and 5 components. In addition, we are also presenting a questionnaire, with specific scoring guidelines, which can be used in any study using storytelling via virtual entity as mean of persuasion.